ANALISIS BIAYA PRODUKSI SEBAGAI ALAT PENGENDALIAN BIAYA PADA CV BUDI LUXINDO LAMPUNG - R u d y - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
Standard cost system acts as a controlling production costs. Standard cost system is a costaccounting system that processes information so that management costs can detect the activities ofthe company which costs deviate from the prescribed standard costs.This research uses descriptive evaluative approach to technique documentation. Theanalysis technique used is the qualitative and quantitative analysis. Descriptive evaluative method,which analyzes the data in a way to describe or depict the data collected as it is without intending tomake general conclusions apply (generalization). This quantitative analysis using analytical variance,which analyzes the actual costs to the cost deviation standard.The results of analysis of variance calculation using full costing approach, has acquired thetotal deviation / difference that occurs in the production costs of processing the Palm Acid Oil (PAO)of Rp 177,050,000.00. This is a difference of adverse happens to the cost of production Budi LuxindoCV. This is evidenced in the results of calculations in which the actual production cost incurred isgreater than the cost of production in standardize. And raw material costs are costs that have adominant influence on the occurrence of such difference.